(untitled) (Economic and Political Thought, 2017)
The article presents the relations between the Federal Republic of Germany and six member states of the Eastern Partnership programme, i.e. Ukraine, Belarus, Armenia, Azerbaijan and Georgia. The analysis also covers the attitude of the German federal government towards the Eastern Partnership project as such, which was a Polish initiative supported by Sweden. The article also takes into consideration the implications of the German eastern policy carried out in the region for Poland.